Peran Dan Fungsi Sat Sabhara Polres Banjar dalam Pelaksanaan Patroli - Iskandar, Alpin; Putra, Hendri Darma; Anggraeni, Happy Yulia (Law Study Program, Faculty of Law, Nusantara Islamic University, 2020)
This research is motivated by the increase in the crime rate in the Banjar Police jurisdiction in 2020, which was 27 (twenty seven) cases compared to the previous year which amounted to 14 (fourteen) cases. The data shows that the performance of the Banjar Police Sat Sabhara in carrying out patrol duties has experienced a decline. The method used in this study is a normative juridical approach, namely testing and reviewing secondary data. This research was conducted in two stages, namely library research and field research which is only supporting. The results of the study show that based on Article 55 paragraph (1) of the National Police Perkap No. 23 of 2010, Sat Sabhara has a position as an element of implementing the main tasks under the Chief of Police. As an implementing element for the main task, the Sat Sabhara has a role and function in terms of maintaining Kamtibmas through regulating, guarding, patrolling, escorting and community service activities and early-stage enforcement efforts. There are several obstacles faced by Sat Sabhara in carrying out patrol activities, namely the lack of good planning and the less than optimal implementation of patrols. The efforts that must be made are to evaluate planning and maximize patrol activities by increasing the number of human resources and adding facilities and infrastructure to support activities.Penelitian ini dilatarbelakangi oleh meningkatnya angka kriminalitas di wilayah hukum Polres Banjar pada tahun 2020 yaitu sebanyak 27 (dua puluh tujuh) kasus dibanding tahun sebelumnya yang berjumlah sebanyak 14 (empat belas) kasus. Data tersebut menunjukan kinerja Sat Sabhara Polres Banjar dalam melaksanakan tugas patroli mengalami kemunduran. Metode yang digunakan dalam penelitian ini adalah pendekatan yuridis normatif, yaitu menguji dan mengkaji data sekunder. Penelitian ini dilakukan melalui dua tahap yaitu studi kepustakaan dan penelitian lapangan yang hanya bersifat penunjang. Hasil penelitian menunjukan bahwa berdasarkan Pasal 55 ayat (1) Perkap Polri No. 23 Tahun 2010, Sat Sabhara mempunyai kedudukan sebagai unsur pelaksana tugas pokok yang berada di bawah Kapolres. Sebagai unsur pelaksana tugas pokok, Sat Sabhara mempunyai peran dan fungsi dalam hal pemeliharaan Kamtibmas melalui kegiatan pengaturan, penjagaan, patroli, pengawalan serta pelayanan masyarakat dan upaya penindakan tahap awal. Ada beberapa hambatan yang dihadapi Sat Sabhara dalam melaksanakan kegiatan patroli yaitu kurangnya perencanaan yang baik dan kurang maksimalnya pelaksanaan patroli. Adapun upaya yang harus dilakukan adalah melakukan evaluasi perencanaan dan memaksimalkan kegiatan patroli dengan meningkatkan jumlah SDM dan menambah sarana dan prasarana penunjang kegiatan.